MANAJEMEN KEUANGAN PENDIDIKAN MASA PANDEMI COVID-19 DI SMPN 1 PANCATENGAH - nurbani, fitri; ruhimat, agus; robiansyah, diky (Journal of Management Review, 2025)
This study aims to describe educational financial management from planning, implementation, to financial supervision during the Covid-19 pandemic which is certainly very interested in research. The approach in this study uses a qualitative research approach with a case study method. Data collection techniques using interviews, observation, and documentation. The research location is in SMP Negeri 1 Pancatengah. The subjects in the study were principals, committees, school treasurers, and teachers. Based on the findings, that during the Covid-19 pandemic, the implementation of financing focused on purchasing medical equipment, honoring teachers and rejuvenating schools such as repainting and maintaining school buildings. The impact of the Covid 19 pandemic on SMPN 1 Pancatengah is very clear, the use of the budget is adjusted to the need to deal with the covid-19 outbreak. In terms of reporting or the use of BOS funds, according to the head of SMPN 1 Pancatengah, during the Covid 19 pandemic, the leniency is not the same as normal.